How Does a Salesperson Improve their Performance? The Importance Role of Customer Smart Response Capability - Diana Aqmala; Elia Ardyan (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
A salesperson is the part of a company who will always meet its customers. A salesperson should have the capability of responding to the customers. This research aims at examining the importance of the salesperson’s customer smart response capability for the insurance industry in Indonesia. The respondents in this research are 317 salespeople who work in the insurance industry. This research uses structural equation modeling to process its data. The results of this research show the importance of the customer smart response capability in the insurance industry. This customer smart response capability can improve a salesperson’s performance. Additionally, the customer smart response capability mediates the influence of customer sensing on the salesperson’s performance and mediates the influence of sales training’s effectiveness on the salesperson’s performance.